2020
DOI: 10.3390/ijerph17218231
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction among Young Adult University Students: The Complex Interplay between Family Functioning, Impulsivity, Depression, and Anxiety

Abstract: International research has underlined that both interpersonal, self-regulation, and comorbid variables can lead to a higher risk of developing internet addiction (IA) among young adults. To date, no studies have explored the interplay between young adults’ family functioning, impulsivity, and psychopathological difficulties. In a community sample of 244 young adult university students, this study aims to assess the relationship between young adults’ IA and young adults’ gender, the perception of their family f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 104 publications
5
46
0
2
Order By: Relevance
“…Impulsivity also partially mediated the relationship between PIU and depressive symptoms, since both direct and indirect effects remained significant in the final SEM model. Our results were in line with Bisen and Deshpande (33) and Marzilli et al (32) who reported significant links between PIU and depression, anxiety and impulsivity in students' populations. In the studies by Wang et al (34) and Zhang (31) impulsivity was also a significant marker for PIU in the students.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Impulsivity also partially mediated the relationship between PIU and depressive symptoms, since both direct and indirect effects remained significant in the final SEM model. Our results were in line with Bisen and Deshpande (33) and Marzilli et al (32) who reported significant links between PIU and depression, anxiety and impulsivity in students' populations. In the studies by Wang et al (34) and Zhang (31) impulsivity was also a significant marker for PIU in the students.…”
Section: Discussionsupporting
confidence: 93%
“…However, the study by Zhang ( 31 ) comprising 459 undergraduate students in China found that impulsivity in particular mediated the relationship between PIU and neuroticism ( 31 ). A recent Italian study involving 244 university students found that PIU was associated with high attentional impulsivity and depressive symptoms ( 32 ). The same relationships were observed in the study analyzing data of 1,600 Indian college students which provided evidence of associations between PIU symptoms of depression, anxiety and impulsivity ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alamgir et al found that IA has no relation to gender but has a negative association with physical activity (19). Marzilli et al concluded similar results (20). However, a recent meta-analysis showed that male Chinese college students (16%) have a higher rate of IA than their female counterparts (8%) (12).…”
Section: Introductionmentioning
confidence: 99%
“…[22] As we have already known, the cause of internet addiction is rather complex. [23]. As shown by the aforementioned documents, one study revealed that people with internet addiction tended to showed high motivation for anonymity, simpli ed communication, emotional support, social compensation and escapism [24], particularly motivation for escapism was predominantly found in online gaming [25].…”
Section: Introductionmentioning
confidence: 98%